122 Physiological effects of low level laser therapy on exercised horses. (28th November 2020) - Rosenkrans, Ashley; Freeman, Carson; Oberhaus, Erin L; Dias Morse, Palika; Rosenkrans, Charles
Abstract: Low level laser therapy (LLLT) is a form of phototherapy which may stimulate healing of injuries and lesions from exercise. Our objective was to determine effects of LLLT before or after exercise on equine serum concentrations of cortisol, lactate, and cytochrome P450 (CYP) inhibition. Twelve quarter horses were randomly assigned to one of three groups: (A) received no laser therapy, (B) received six minutes of laser therapy before exercise, and (C) received six minutes of laser therapy after exercise. Laser (635 nm) treatment was with a class II handheld low-level laser with constant wave modulation. Horses were exercised using a walker for 30 min five days a week for three weeks, and within 30 min after exercise blood was collected on day 7, 14, and 21; blood was collected on day 0 prior to exercise as a reference point. Serum was collected, frozen; and cortisol, lactate, and CYP inhibition were determined via validated assays. Data were analyzed by ANOVA with horse as the experimental unit; an interaction (P < 0.05) between treatment group and day of study affected serum concentrations of cortisol, lactate, and CYP inhibition. For group B horses, cortisol concentrations decreased (P < 0.001) from day 14 to day 21 (31 vs 20 ± 2.9 ng/mL). Serum lactate concentrations increased (P < 0.0001) during the three weeks of training (2700, 2773, 3064, and 6061 ± 232 μM; respectively for day 0, 7, 14, and 21); whereas, inhibition of CYP decreased (P < 0.01) from day 0 to day 21. Interaction of main effects on lactate can be explained by larger increases in lactate concentrations for horses treated with LLLT during the trial; conversely, CYP inhibition decreased for horses treated with LLLT after exercise. Our results suggest that LLLT may be useful in improving performance of equine athletes.